Association between oral leukoplakia and risk of upper gastrointestinal cancer death: A follow‐up study of the Linxian General Population Trial. Issue 6 (20th September 2017) - Liang, He; Yang, Zhao; Wang, Jian‐Bing; Yu, Pei; Fan, Jin‐Hu; Qiao, You‐Lin; Taylor, Philip R.
Abstract : Background: This study was conducted to explore the association between oral leukoplakia (OL) and the risk of upper gastrointestinal cancer death in the Linxian General Population Trial Cohort. Methods: A prospective cohort study of the Linxian General Population Trial Cohort was performed. Participants with OL were treated as an exposed group, and the remainder was selected as a control group. All subjects were followed monthly by village health workers and reviewed quarterly by the Linxian Cancer Registry. Hazard ratios (HRs) and 95% confidence interval (CIs) were evaluated using proportional hazard and proportional subdistribution hazard models, respectively. Results: Over a median of 27 years of observation, 29 476 subjects were followed‐up. A total of 17 473 deaths occurred, including 2345 esophageal squamous cell carcinoma (ESCC), 1139 gastric cardia carcinoma, and 506 gastric non‐cardia carcinoma deaths. Significant increased ESCC mortality was observed in subjects with OL (exposed 9.66% vs. unexposed 7.39%; P  < 0.0001). Furthermore, subjects with OL had a 22% higher risk of death from ESCC (HR 1.22, 95% CI 1.10–1.34; P  = 0.0001) after adjusted covariates. In subjects aged ≤52 at the baseline, OL was significantly associated with an elevated risk of ESCC mortality (HR 1.32, 95% CI 1.13–1.54 ; P = 0.0005). No significant associations were observed for gastric cardia carcinoma and non‐cardia carcinoma mortality. Conclusions: OL may increase the risk of ESCC mortality, especially in the younger population. These associations should be investigated in further studies.